Pengaruh BI-Rate, Kurs USD terhadap Pengaruh Timbal Balik antara Return Saham dan Trading Volume - Silvia Hendrayanti (Jurnal Ilmiah Aset, 2018)
The objectives of this research to analyze the influence of BI Rate, Exchange Rate of mutual effect between Return of stock and trading volume (Study on Stock of Mining Sector that listed on Indonesia Stock Exchange in 2007 – 2015 periods). Population in this research is the mining sector in Indonesia during the observation period January 2007 until December 2015 (data from BEI and Indonesian Bank monthly published on BEI). Totality of the sample which has been used in this study was 108 samples which consists of 52 issuers. In this study, the research method is by using descriptive analysis, stationary test, VAR analysis, Granger causality test, Impulse response anlysis, and variance decomposition analysis. Hypothesis test, and R2 test.The result of this research shows that BI Rate variable has a negative and significant to stock return, exchange rate variable has a positive and not significant to stock return, BI Rate variable has a negative and significant to Trading volume, Exchange rate variable has a negative and not significant to Trading volume, Stock return(-1)& Stock return(-2) variable has a positive and significant to Trading volume, Trading volume(-1)& Trading volume(-2) variable has a negative and not significant to stock return.